Ibâḍî Reformism in Twentieth-Century Algeria : The Tafsîr of Shaykh Ibrâhîm Bayyûḍ - Valerie Hoffman; Sulaiman bin Ali bin Amir al-Shueili (Revue des Mondes Musulmans et de la Méditerranée)
Shaykh Ibrâhîm b. ‘Umar Bayyûḍ of Wâdî Mzâb (1899-1981), leader of Ibâḍî reformism in Algeria after the death of Muḥammad b. Yûsuf Aṭfiyyash (1820-1914), delivered a public commentary on the Qur’an from 1935-1980, which was recorded beginning with Sûra 17:70. Shaykh Bayyûḍ claimed to follow the goals and methodology of Muḥammad ‘Abduh and Rashîd Riḍâ’s Tafsîr al-Manâr. This article analyzes Shaykh Bayyûḍ’s commentary in comparison to, on the one hand, Aṭfiyyash’s two Qur’an commentaries (Hamayân al-zâd ilâ dâr al-ma‘âd and Taysîr al-tafsîr), in order to determine its relationship to earlier modern Ibâḍî reformism, and, on the other hand, to Tafsîr al-Manâr, in order to determine its relationship to that strand of Sunni reformism. It finds that Bayyûḍ’s commentary, like Tafsîr al-Manâr, promotes Islamic unity and eschews theological dogmatism, while attacking customs deemed antithetical to Islamic teaching and making sometimes lengthy digressions on topics of contemporary social and political importance. Nonetheless, Bayyûḍ remains faithful to Ibâḍî doctrine on topics on which Ibâḍîs and Sunnis differ, and there is little evidence that he argued for Islam’s compatibility with liberal values ; on the contrary, at several points in his commentary he states that modern ideas and customs constitute a real threat to Islam.